Selection and Yield Formation Characteristics of Dry Direct Seeding Rice in Northeast China - Chao Liang; Yimeng Li; Kunhao Zhang; Zhouzhou Wu; Jiaxin Liu; Junfeng Liu; Chanchan Zhou; Shu Wang; Fenghai Li; Guomin Sui (Plants, 2023)
Dry direct seeding rice (DSR) is an emerging production system because of increasing labor and water scarcity in rice cultivation. The limited availability of rice cultivars suitable for dry direct seeding hampers the widespread adoption of this cultivation method in Northeast China. This study aimed to investigate grain production and plant characteristics associated with dry direct seeding rice. We conducted a field experiment on 79 japonica rice cultivars in Shenyang City, Liaoning Province, Northeast China, in 2020 and 2021. This study found that the grain yield of the tested rice cultivars ranged from 5.75–11.00 t ha−1, with a growth duration lasting between 144–161 days across the cultivars. These cultivars were then categorized into high yielding (HY), medium yielding (MY), and low yielding (LY) based on daily yield by using Ward’s hierarchical clustering method. The higher grain yield for HY compared to MY and LY was attributed to more spikelets per unit area. The HY alleviated the conflict between higher panicle density and larger panicle size by improving the seedling emergence rate and productive stem rate. It also significantly increased shoot biomass at maturity. The HY reduced the period between seeding and beginning of heading (BBCH 51) and the proportion of dry matter partitioned to the leaf at the heading stage. However, it also increased the accumulation of dry matter in the grain and the proportion of dry matter partitioned to the grain at maturity. Furthermore, the HY markedly increased the harvest index and grain-leaf ratio, which are beneficial to coordinate the source–sink relationship. A quadratic function predicted that 98 days is the optimum growth duration before heading (BBCH 51) for achieving maximum yield. In conclusion, for dry direct seeding rice, it is appropriate to select high-yielding japonica inbred rice cultivars with shorter growth duration before heading (about 93–102 day), higher panicle number (about 450–500 × 104 ha–1), more spikelet number per panicle (about 110–130), higher seedling emergence rate (about 70–75%), higher productive stem rate (about 60–70%), and greater harvest index (about 50–55%).